“Key Product” a Fuzzy Logic-based New Approach for Determining Consumer Preferences - Çavdar, Ertuğrul (International Journal of Contemporary Economics and Administrative Sciences, 2017)
<!–[if gte mso 9]> <![endif]–> Nowadays, intense competition necessitates the continuous monitoring of target audiences in order to harmonize goods and services with consumer expectations. Many studies have been conducted on the selection criteria for goods and services, levels of perception and expectation of consumers. In this study, a fuzzy logic-based new quantitative analysis method was used to help assess the extent to which current smart phones satisfy consumer expectations, and determine the most suitable combination of product features according to general consumer preferences. The study population consisted of university students. In this context, the study sample was specifically composed of the students from the Yuzuncu Yil University in Van, Turkey. The study questionnaire administered to 386 students was based on the applications of smart phone. Using “Key Product” method analysis performed based on the results of this study, it will be easier and more functional to identify consumers whose preferences are not satisfied in the market, and offer new and suitable combinations for them. In addition, and depending on the number of products to be produced and the consumer demands to be met, this method will also make it easier to determine the number of products with which production processes should be initiated, and the duration of time for which the production stages should be continued. Proposed fuzzy logic-based new quantitative analysis method determines the most suitable combination of product features according to general consumer preferences. <!–[if gte mso 9]> Normal 0 21 false false false TR X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>